Higher Fuel and Food Prices : Impacts and Responses for Mozambique - World Bank (Washington, DC, 2014)
The dramatic increases in world food and fuel prices during 2007 and early 2008 may set back Mozambique's considerable advances in poverty reduction during the past decade. This study assesses the impact of higher fuel and food prices at both household and macroeconomic levels, and also considers policy options to mitigate some of the negative impacts of higher prices. Rising world prices certainly represents a negative terms-of-trade shock for Mozambique, since the country imports almost all of its fuel and is a net importer of food. The report is structured in six sections. Section two presents information on the extent of international food and fuel price increases and their transmission to local markets in Mozambique. Section three presents household-level analysis focused on the first order impact of the food price increases. Section four complements previous sections by examining the impact of higher food and fuel prices within a general equilibrium framework. Section five discusses the likely impact of alternative policy options in the short and long term. Section six summarizes and concludes.